Symptom severity in burning mouth syndrome associates with psychological factors - Heli Forssell; Tuija Teerijoki-Oksa; Pauli Puukka; Ann-Mari Estlander (WILEY, 2022)
Burning mouth syndrome (BMS) patients are psychologically distressed, but whether this associates with symptom severity is unclear. The aim was to investigate the association of psychological factors with pain intensity and interference in BMS. Fifty-two women (mean age 63.1, SD 10.9) with BMS participated. Pain intensity and interference data were collected using 2-week pain diaries. Psychological factors were evaluated using Depression Scale (DEPS), Pain Anxiety Symptom Scale (PASS) and Pain Vigilance and Awareness Questionnaire (PVAQ). The local ethical committee approved the study. Patients were divided into groups based on pain severity distribution tertiles: low intensity (NRS <= 3.7) or interference (NRS <= 2.9) (tertiles 1-2, n = 35) and moderate to intense intensity (NRS > 3.7) or interference (>2.9) (tertile 3, n = 17). T test, Wilcoxon's test and Pearson's correlation coefficient were used in the analyses. Patients in the highest intensity and interference tertiles reported more depression (P = .0247 and P = .0169) and pain anxiety symptoms (P = .0359 and P = .0293), and were more preoccupied with pain (P = .0004 and P = .0003) than patients in the low intensity and interference groups. The score of the pain vigilance questionnaire correlated significantly with pain intensity (r = .366, P = .009) and interference (r = .482, P = .009). Depression (r = .399, P = .003) and pain anxiety symptoms (r = .452, P = .001) correlated with pain interference. Symptom severity in BMS associates with symptoms of psychological distress emphasising the need to develop multidimensional diagnostics for the assessment of BMS pain.